2008
DOI: 10.1121/1.2935743
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the tyre to further lowering tyre/road noise

Abstract: The tire is the only part of a vehicle that must be originally and primarily designed to transmit forces to outside the vehicle, and the amount of energy a tire consumes per kilometer in operation and for production has to be minimized. The tire manufactures are searching for many years for a construction, which fulfils the targets of the automotive industry and generates less noise. On dry, wet and snow-covered roads, the safety of traffic can only be ensured by sufficient capability for acceleration and brak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…17,18 A tire tread rubber of this quasi-sinusoidal response to oscillatory deformation can provide a quiet and comfortable driving experience, as the rolling noise and traction of tire tread under torque is closely associated with the damping coefficient (tan δ = G″/G″) measured in the nonlinear regime. 19 Despite the technological significance of this phenomenon, the underlying cause of the linear-nonlinear dichotomy of the rheological response of filled rubbers in the nonlinear regime has been a long-term puzzle. 13,16 In particular, this phenomenon is not observed in some other particle-filled materials, such as colloidal gels, suspensions, emulsions, and paste materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 A tire tread rubber of this quasi-sinusoidal response to oscillatory deformation can provide a quiet and comfortable driving experience, as the rolling noise and traction of tire tread under torque is closely associated with the damping coefficient (tan δ = G″/G″) measured in the nonlinear regime. 19 Despite the technological significance of this phenomenon, the underlying cause of the linear-nonlinear dichotomy of the rheological response of filled rubbers in the nonlinear regime has been a long-term puzzle. 13,16 In particular, this phenomenon is not observed in some other particle-filled materials, such as colloidal gels, suspensions, emulsions, and paste materials.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of a “linear-nonlinear dichotomy” epitomizes an idealized state from a rheological perspective. This characteristic is amenable to the construction of models designed to describe more complex rheological behaviors exhibited by filled rubbers. , While no material exhibits behavior that aligns perfectly with the ideal state, numerous filled rubber compounds demonstrate such a close approximation that the “dichotomy” concept proves to be invaluable in a multitude of practical applications. Fourier transform (FT) analysis shows that in the investigations of particle-filled rubbers, , higher-order harmonics can sometimes be detected by a sensitive rheometer, but they are usually very small and negligible. The ratio of the third to the first harmonic responses I 3 / I 1 in the range when G ′ loses 80% of its value in the linear regime and G ″ passes through its maximum is typically less than 3%, and sometimes even less than 1%. , As a result, the relationships between the dynamic moduli and the average energies stored and dissipated per cycle per unit volume and their physical meaning are still applicable in the nonlinear regime of filled rubbers. In rubber industries, this unique feature has been used widely by engineers and compounders in the design, characterization, and application of rubber products .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seamann showed that more grooves increase the water storage capacity improving the hydroplaning performance. At the same time the extra grooves result in more variations of the contact pressure increasing the noise and wear [168]. Tyre development is therefore often a matter of finding the correct compromise between the tyre performances.…”
Section: Tyre Performancesmentioning
confidence: 99%
“…The tread stiffness also affects the noise. Sandberg [176] and Saemann [169] reported a noise increase of around 2.5 dB(A) for 10 units increase in Shore A tread rubber hardness. Bekke [16] on the other hand used the physical quantities stiffness or storage modulus E and the loss modulus E in the statistical correlation.…”
Section: Tread Pattern (Radial) Excitation *mentioning
confidence: 99%